Time of day of exercise does not affect the beneficial effect of exercise on bone structure in older female rats - Cao, Jay J.; Gregoire, Brian R. (Frontiers in Physiology, 2023)
Background: Circadian clock genes are expressed in bone and biomarkers of bone resorption and formation exhibit diurnal patterns in animals and humans. Disruption of the diurnal rhythms may affect the balance of bone turnover and compromise the beneficial effects of exercise on bone. Objective: This study investigated whether the time of day of exercise alters bone metabolism in a rodent model. We hypothesized that exercise during the active phase results in greater bone mass than exercise during the rest phase in older female rats. Methods: Fifty-five, female 12-mo-old Sprague Dawley rats were randomly assigned to four treatment groups (n = 13-14/group). Rats were subjected to no exercise or 2 h of involuntary exercise at 9 m/min and 5 d/wk for 15 wk using motor-driven running wheels at Zeitgeber time (ZT) 4-6 (rest phase), 12-14 (early active phase), or 22-24 (late active phase). ZT 0 is defined as light on, the start of the rest phase. A red lamp was used at minimal intensity during the active, dark phase exercise period, i.e. ZT 12-14 and 22-24. Bone structure, body composition, and bone-related cytokines in serum and gene expression in bone were measured. Data were analyzed using one-way ANOVA followed by Tukey-Kramer post hoc contrasts. Results: Exercise at different ZT did not affect body weight, fat mass, lean mass, the serum bone biomarkers, bone structural or mechanical parameters, or expression of circadian genes. Exercise (pooled exercise data from different ZT were compared to the No-Exercise data (a priori contrast) increased serum IGF-1 and irisin concentrations, compared to No-Exercise. Exercise increased tibial bone volume/total volume (P = 0.01), connectivity density (P = 0.04), and decreased structural model index (P = 0.02). Exercise did not affect expression of circadian genes. Conclusions: These data indicate that exercise is beneficial to bone structure and that the time of day of exercise does not alter the beneficial effect of exercise on bone in older female rats.